Navigating Compliant Agency in Cyberspace: Muslim Womanhood Through the Lens of Oki Setiana Dewi - Luthfia, Asya Dwina (Fakultas Agama Islam, Universitas Muhammadiyah Yogyakarta, 2024)
In contrast to the stereotype that docile Muslim women are confined to domestic roles, this study examines how Muslim womanhood can balance economic independence with adherence to religious and societal expectations. Focusing on the case of Indonesian ustadzah (Islamic preacher) Oki Setiana Dewi, this research explored her agency as expressed through her Instagram activity. Cultivating the compliant agency, this article asserts that consciously adhering to religious values preserves patriarchal expectations while gaining authority and financial freedom. This study utilized qualitative content analysis, collecting data from Oki’s Instagram account using